Assessing psychiatric disorder with a human interviewer or a computer. Issue 2 (April 1994) - Lewis, G
Abstract : OBJECTIVE–To compare a self administered computerised assessment of neurotic psychiatric disorder (psychiatric morbidity) with an identical assessment administered by a human interviewer. In particular, to discover whether a computerised assessment overestimates or underestimates the prevalence of psychiatric morbidity in relation to a human interviewer. SETTING–A health centre in south east London, UK. SUBJECTS–A non-consecutive series of health centre attenders. Complete data were available on 92 subjects. DESIGN–All subjects received both assessments on the same occasion but were randomised to receive either the computerised assessment first or the human interview first. RESULTS–The mean total score on the assessment was the same for both methods of administration; computer 8.77 v human 8.69 (95% confidence interval for difference -0.70, 0.87). The correlation between the human and interviewer assessments was 0.91. CONCLUSION–Self administered computerised assessments are valid, unbiased measures of psychiatric morbidity. In addition to their use as a research tool, they have potential uses in primary care including screening for psychiatric morbidity and in forming the basis for clinical guidelines.